A retrospective case-control hospital based study on the diagnostic utility of anti-cyclic citrullinated peptide antibodies in comparison with rheumatoid factor, C-reactive protein and erythrocyte sedimentation rate as a diagnostic inflammatory biomarker - Dr. Pratibha Shamanna; Dr. Arundhathi S.; Praveen Kumar R.; Vanishree (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease, characterised by persistent joint inflammation resulting in joint damage and disability. Diagnosis of RA is primarily on clinical manifestations and radiological findings due to lack of reliable diagnostic tests. As substantial joint damage occurs before patient presents clinically, a validated biomarker is required forits early detection. Objectives: To compare diagnostic utility of laboratory variables like anti–cyclic citrullinated peptide(Anti-CCP) antibodies, Rheumatoid factor (RF), C-reactive protein (CRP)and Erythrocyte sedimentation rate(ESR)in patients with Rheumatoid arthritis(RA). Materials and Methods: Blood from 80 clinically suspected RA patients and 80 age and sex matched healthy controls were tested for Anti-CCP antibodies, RF, CRP and ESR. Diagnostic properties of Anti-CCP in comparison with RF, CRP and ESR were statistically analysed and p value<0.05 was considered significant. Results: Anti-CCP was 100% positive in test group and 100% negative in control group with p value <0.001. Correlation between Anti-CCP and RF and Anti CCP and CRP showed significant titres with p value <0.001. Anti-CCP was 100% sensitive and 80% specific compared to RF. Conclusion: Anti-CCP is more sensitive and specific than other tests available for diagnosis of RA. Combined detection of all four parameters is valuable in confirming diagnosis of RA. Recognition of utility of such biomarkers is essential to gain insight into activity of this disease, which is vital for early management to limit consequential morbidity and to improve quality of life.